The hypoxia-inducible factor-responsive proteins semaphorin 4D and vascular endothelial growth factor promote tumor growth and angiogenesis in oral squamous cell carcinoma - Zhou, Hua (2012)
Growth and metastasis of solid tumors requires induction of angiogenesis to ensure the delivery of oxygen, nutrients and growth factors to rapidly dividing transformed cells. Through either mutations, hypoxia generated by cytoreductive therapies, or when a malignancy outgrows its blood supply, tumor cells undergo a change from an avascular to a neovascular phenotype, a transition mediated by the hypoxia-inducible factor (HIF) family of transcriptional regulators. Vascular endothelial growth factor (VEGF) is one example of a gene whose transcription is stimulated by HIF. VEGF plays a crucial role in promoting tumor growth and survival by stimulating new blood vessel growth in response to such stresses as chemotherapy or radiotherapy-induced hypoxia, and it therefore has become a tempting target for neutralizing antibodies in the treatment of advanced neoplasms. Emerging evidence has shown that the semaphorins, proteins originally associated with control of axonal growth and immunity, are regulated by changes in oxygen tension as well and may play a role in tumor-induced angiogenesis. Through the use of RNA interference, in vitro and in vivo angiogenesis assays and tumor xenograft experiments, we demonstrate that expression of semaphorin 4D (SEMA4D), which is under the control of the HIF-family of transcription factors, cooperates with VEGF to promote tumor growth and vascularity in oral squamous cell carcinoma (OSCC). We use blocking antibodies to show that targeting SEMA4D function along with VEGF could represent a novel anti-angiogenic therapeutic strategy for the treatment of OSCC and other solid tumors.